Development of Some Physical Properties of Cadmium Telluride Coatings Prepared by Spray Pyrolysis - Mishaal, Adyan Hazem; Hamid Mustafa, Mohammed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
For this work, the spray pyrolysis technique is employed to create uniform thin films of cadmium telluride (CdTe) at 350°C on glass substrates. For optical and structural examination, the films that were deposited undergo annealing at 573 K and 723 K. In an air atmosphere, before being examined using an XRD, a microscopy force atomic (AFM), and UV-Vis spectrophotometer. The film’s cubic structure and polycrystalline nature were demonstrated by the XRD tests with preferred orientation (111), and temperatures for annealing improve crystalline speed. Crystallite size and microstrain were among the microstructural metrics that were computed with an increase in annealing temperatures; it was found that the microstrain decreased and the crystallite size increased. In the transmittance’s strong absorption region, the basic optical parameters, including the band gap and absorption coefficient, were computed. The optical transition in these coatings was discovered to be a direct transfer, while the energy band gap is shown to decrease with annealing, while increases in optical absorbance.